Contemporary federalist thought in Quebec : historical perspectives - Desaulniers, Antoine Brousseau; Savard, Stéphane; Baker, Mary, translator; Laforest, Judith, translator; O'Hearn, Lawrence, translator; Rodrigue, Eric, translator (Democracy, diversity, and citizen engagement series, 2023)
"Quebec's most recent attempts to assert its distinctiveness within Canada have relied on unilateral constitutional means to strengthen its French and secular character, suggesting that an important change of political culture has taken place in Quebec. With its diverse team of researchers, Contemporary Federalist Thought in Quebec considers the recent history of the debate that once threatened Canada with disjunction, exploring the federalist thought that continues to shape constitutional debate in Quebec. Examining historical perspectives from 1950 to the present day, the volume draws portraits of the key actors in the federalist movement--including political leaders, intellectuals, academics, activists, and spokespersons for pressure groups--comparing their various outlooks, interventions, and values, and examining the ties that bind these actors to the sense of nationalism that emerged during Quebec's Quiet Revolution. Taking a multidisciplinary approach, Contemporary Federalist Thought in Quebec casts new light on the continuing debate surrounding Quebec's place in Canada, and makes strides in giving nuance to what is traditionally conceived as a rigid opposition between sovereigntists and federalists in the province."--